Sofosbuvir and simeprevir combination therapy in the setting of liver transplantation and hemodialysis. Issue 2 (31st January 2015) - Perumpail, R.B.; Wong, R.J.; Ha, L.D.; Pham, E.A.; Wang, U.; Luong, H.; Kumari, R.; Daugherty, T.J.; Higgins, J.P.; Younossi, Z.M.; Kim, W.R.; Glenn, J.S.; et al.
Abstract: We report safety, tolerability, and 12‐week sustained virologic response with half‐standard dose sofosbuvir and standard‐dose simeprevir combination therapy in a hepatitis C virus genotype 1a‐infected liver transplant recipient on hemodialysis – uncharted territory for sofosbuvir‐based therapy. The patient was a non‐responder to prior treatment with pegylated interferon plus ribavirin. Sofosbuvir efficacy was maintained despite pill‐splitting and administration of half‐standard dose, 200 mg per day. No drug–drug interactions were noted with tacrolimus‐based immunosuppression. Laboratory tests remained stable or improved during therapy. Our observation, if reproduced in a larger study, may lead to significant improvement in clinical outcomes and cost savings in this patient population.